Korban Salah Tangkap: Penjebakan Melalui Metode Pembelian Terselubung - Manik, Dekha Aprillia Ronauli; Ravizki, Eka Nanda (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The violation of laws in all regulations related to the illicit trafficking of narcotics is an element of Narcotics Crime, which is one form of a crime that is extraordinary in nature. This makes Narcotics Crime a matter that attracts considerable attention from the wider community. Various efforts are made to combat this, one of which is through the implementation of entrapment using undercover buy methods. However, a clear and detailed definition and mechanism of this method are not present in the relevant regulations, leading to confusion in understanding and errors in its implementation. The birth of wrongful arrest victims is related to procedural defects carried out by investigators due to differences in interpretation and understanding. The research method employed is normative juridical, conducted through an examination of legislation, expert opinions, legal theories, and various relevant literature. The results of this research indicate the necessity of regulations regarding the raised topic, as it holds significant urgency